How complete are individualized education programmes developed for students with disabilities served in inclusive classroom settings?. Issue 5 (20th October 2019) - Rakap, Salih; Yucesoy-Ozkan, Serife; Kalkan, Sinan
ABSTRACT: Development of high-quality individualized education programmes (IEP) is vital for students with disabilities. Although legislations and literature provide guidelines for which components to be included in IEPs, there is limited research about whether these components are actually included in IEPs developed for students with disabilities served in inclusive classrooms in Turkey. In this study, we explored the extent to which IEPs include components required by laws and regulations in Turkey and those recommended by inclusive education literature and whether there was a relationship between student characteristics and percentages of legal or recommended components included in IEPs. We evaluated 206 IEPs obtained from 60 inclusive elementary schools located in 26 different cities. We developed an IEP Component Checklist to evaluate whether IEPs included legal requirements and recommended components. Descriptive findings of the study demonstrated that IEPs failed to include majority of legal requirements and recommended components. Correlational findings indicated that percentages of legal requirements or recommended components included in IEPs were not associated with student characteristics. Findings were discussed in relation to the extant literate and recommendations for future research and practice were provided.